Routing Protocols for Vehicular Delay Tolerant Networks: A Survey - Kang, Hyunwoo; Ahmed, Syed Hassan; Kim, Dongkyun; Chung, Yun-Su (International journal of distributed sensor networks, 2015)
Recently, the delay tolerant networks (DTN) have been utilized in various operational communication paradigms. This includes the communication scenarios that are subject to disruption and disconnection as well as the scenarios with high delay and frequent partitioning, that is, vehicular ad hoc networks (VANETs). Due to the several characteristics match, new research paradigm named as vehicular delay tolerant networks (VDTNs) is introduced. Through relays and store-carry-forward mechanisms, messages in VDTNs can be delivered to the destination without an end-to-end connection for delay-tolerant applications. However, the choice of routing algorithms in VDTNs is still under study. The main objective of routing protocols in VDTNs is to maximize the probability of delivery at the destination while minimizing the end-to-end delay. Until now, many routing protocols have been proposed to meet requirements of varying applications. In this paper, we, therefore, provide a detailed study of recently proposed routing schemes for VDTNs. We also perform comparative analysis on the basis of unique criterion such as forwarding metrics with their implementations. In addition, open challenges and future directions are provided to make room of interest for the research community.